Evaluating thermal efficiency and economic impacts in supplying energy demands for direct air capture - Siegel, Madeleine Hope, author; Bandhauer, Todd, advisor; Quinn, Jason, committee member; Herber, Daniel, committee member (Colorado State University. Libraries, 2024)
Direct Air Capture (DAC) technologies that remove CO2 directly from the atmosphere are needed to meet international goals of limiting atmospheric temperature increase before 2100. Operating costs, including the cost of energy inputs, currently limit the rapid deployment of DAC systems. An abundance of untapped and abandoned geothermal resources provides an opportunity to utilize this thermal energy beneath the Earth's surface to reduce the financial and energy costs of DAC. In this study, thermodynamic models of applicable renewable energy scenarios for fulfilling heating and electrical requirements of DAC were analyzed using ASPEN Plus. Individual components were optimized within the geothermal-DAC coupled systems to quantify specific costs of implementation. The results were integrated into a techno-economic analysis (TEA) to provide a holistic perspective to optimize DAC coupled renewable energy systems. The levelized cost of energy (LCOE) for DAC was reduced from $175/t-CO2 removed to as low as $66/t-CO2 removed, guiding large-scale deployment of DAC, and supporting decision-making in the future.
Keywords: direct air capture; techno-economic analysis; ASPEN Plus; thermodynamics; geothermal energy